(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article is about the English hydronyms, its origins, characteristics and types. The geographical names of the British Isles are quite well studied. These islands represent an area with clearly defined natural boundaries. The names that developed in England and the UK as a whole have become widespread in other countries where English is spoken.